Construction of Classical and Nonclassical Fullerenes with Tetrahedral Structure - Sanchez-Bernabe, F.J. (Веснік Брэсцкага ўніверсітэта. Серыя 4. Фізіка. Матэматыка, 2020)
Classical fullerenes are molecules with pentagons and hexagons. On the other hand, nonclassical fullerenes contain also, squared, heptagonal, or octagonal faces.